205k views
5 votes
Calculate the average rate of change over the interval [1, 5] for the following function. H(x)=-2x^2-3x-1

User Seaux
by
5.4k points

1 Answer

5 votes

Answer:


Rate = -15

Explanation:

Given


H(x) = -2x^2 - 3x - 1


[a,b] = [1,5]

Required

The average rate of change

This is calculated using:


Rate = (H(b) - H(a))/(b - a)

Substitute values for a and b


Rate = (H(5) - H(1))/(5 - 1)


Rate = (H(5) - H(1))/(4)

Solve for H(5) and H(1)


H(5) = -2*5^2 - 3*5 - 1 = -66


H(1) = -2*1^2 - 3*1 - 1 = -6

So, the expression becomes:


Rate = (-66 - (-6))/(4)


Rate = (-66 + 6)/(4)


Rate = (-60)/(4)


Rate = -15

User Thijser
by
5.5k points